1975
DOI: 10.1080/0002889758507202
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Metal Inhalation Studies on Miniature Swine

Abstract: Cobalt is considered to be the chief component in the tungsten carbide mixture responsible for hard-metal disease. An animal inhalation study was undertaken simulating conditions under which these workers in the tungsten carbide industry are exposed to cobalt. In this semichronic study, miniature swine were exposed to an inhalation of pure cobalt metal powder at concentrations of 0.1% mg/m3 (present TLV) and 1.0 m/m3. At peroidic intervals, the following studies were performed: pulmonary function tests, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 0 publications
0
18
0
5
Order By: Relevance
“…Since the first recognition of adverse health effects from WC-Co exposure in the 1960s (Trautmann, 1958; Bech et al , 1962; Heuer, 1962; Beritic et al , 1963; Joseph, 1968), there have been a number of reports regarding the toxicity of WC-Co in the literature both in vitro (Edel et al , 1990; Lison and Lauwerys, 1990; Lison and Lauwerys, 1992; Lison and Lauwerys, 1993; Lison et al , 1995; Anard et al , 1997; Antonini et al , 2000; Roesems et al , 2000; Fedan and Cutler, 2001; De Boeck et al , 2003b; Lombaert et al , 2008; Bastian et al , 2009; Ding et al , 2009; Kuhnel et al , 2009; Busch et al , 2010; Zhang et al , 2010; Lombaert et al , 2012) and in vivo (Kerfoot et al , 1975; Kitamura et al , 1980; Lasfargues et al , 1992; Huaux et al , 1995; Lasfargues et al , 1995; Adamis et al , 1997; Rengasamy et al , 1999; De Boeck et al , 2003a). While it is well established that composite WC-Co particles are more toxic than tungsten (W), tungsten carbide (WC) or cobalt (Co) alone, the potential contribution of WC-Co particle internalization toward observed toxicity and the mechanism by which WC-Co particles could be internalized by relevant cells has not been well-addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first recognition of adverse health effects from WC-Co exposure in the 1960s (Trautmann, 1958; Bech et al , 1962; Heuer, 1962; Beritic et al , 1963; Joseph, 1968), there have been a number of reports regarding the toxicity of WC-Co in the literature both in vitro (Edel et al , 1990; Lison and Lauwerys, 1990; Lison and Lauwerys, 1992; Lison and Lauwerys, 1993; Lison et al , 1995; Anard et al , 1997; Antonini et al , 2000; Roesems et al , 2000; Fedan and Cutler, 2001; De Boeck et al , 2003b; Lombaert et al , 2008; Bastian et al , 2009; Ding et al , 2009; Kuhnel et al , 2009; Busch et al , 2010; Zhang et al , 2010; Lombaert et al , 2012) and in vivo (Kerfoot et al , 1975; Kitamura et al , 1980; Lasfargues et al , 1992; Huaux et al , 1995; Lasfargues et al , 1995; Adamis et al , 1997; Rengasamy et al , 1999; De Boeck et al , 2003a). While it is well established that composite WC-Co particles are more toxic than tungsten (W), tungsten carbide (WC) or cobalt (Co) alone, the potential contribution of WC-Co particle internalization toward observed toxicity and the mechanism by which WC-Co particles could be internalized by relevant cells has not been well-addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Although cobalt itself was originally considered the causative agent of HMLD, several studies demonstrated that this is not the case and the disease mainly develops due to the simultaneous presence of WC with Co. 71,74,[76][77][78][79]90,91 It is currently understood that the combination of WC-Co is more toxic than Co, W, or WC particles alone, both in vitro and in vivo, 71,72,74,78,79,81,85,90,91,93,94,[97][98][99] but the reason for this enhanced toxicity is still not well defined.…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
“…KERFOOT et al [18] exposed mini-pigs for 3 months to cobalt concentrations of 0.1 and 1.0 mg·m -3 . In view of a possible involvement of an immunological mechanism (a type I allergic reaction has been suggested in cobalt asthma), they first submitted the animals to a "sensitization" period by inhalation.…”
Section: Animal Studiesmentioning
confidence: 99%